2018
DOI: 10.1152/ajpgi.00102.2018
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of endoplasmic reticulum stress by 4-phenylbutyric acid prevents vital organ injury in rat acute pancreatitis

Abstract: The present study demonstrated that 4-PBA protected pancreas, lung, liver and kidney from injury in rat acute pancreatitis by regulating endoplasmic reticulum stress and mitigating inflammatory response to restrain cell death, and further suggested that 4-PBA may have potential therapeutic implications in the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 36 publications
(37 reference statements)
2
16
0
Order By: Relevance
“…Xu et al [25] demonstrated that SPB can suppress the expression of TNF-α, IL-1β, and IL-6, and can reduce neutrophil infiltration in mice liver. In the present study, as a kind of nutritional compound, SPB had no obvious inflammatory responses in MAC-T cells; however, pretreatment with SPB significantly decreased the expression of three pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6) in LTA-stimulated MAC-T, which is in agreement with previous studies [23,24,25].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Xu et al [25] demonstrated that SPB can suppress the expression of TNF-α, IL-1β, and IL-6, and can reduce neutrophil infiltration in mice liver. In the present study, as a kind of nutritional compound, SPB had no obvious inflammatory responses in MAC-T cells; however, pretreatment with SPB significantly decreased the expression of three pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6) in LTA-stimulated MAC-T, which is in agreement with previous studies [23,24,25].…”
Section: Discussionsupporting
confidence: 93%
“…Cytokines, an essential component of inflammatory mediators, play a crucial role in the process of inflammation. Hong et al [23] found that SPB decreased the levels of pro-inflammatory TNF-α and IL-1β in serum of rat with acute pancreatitis. Zeng et al [24] showed that SPB reduced the release of the pro-inflammatory mediators, IL-1β, TNF-α and IL-6, and significantly inhibited lipopolysaccharide (LPS)-activated endoplasmic reticulum (ER) stress in A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…ER transmembrane proteins sense the folding state of proteins inside the ER lumen and convey the information to the mitochondria and the cytosol. 4-PBA, an ERS inhibitor, acts as a chemical chaperone assisting protein folding in the ER as well as in the cytosol and the mitochondria [47]. In our results, inhibition of ROS with antioxidant NAC and mitigation of ERS with ERS inhibitor 4-PBA obviously suppressed ADE-induced apoptosis and the expression of ERS-related proteins.…”
Section: Discussionsupporting
confidence: 56%
“…Pancreas Immunostaining. Sections for immunostaining were processed with previous methods [18]. After deparaffinization, hydration, antigen retrieval, and serum blocking, the sections were incubated overnight at 4°C with primary antibodies: MPO (1 : 400, Servicebio, Wuhan, China, Cat no.…”
Section: Pancreatic Injury Assessmentmentioning
confidence: 99%